2020
DOI: 10.20885/ejem.vol12.iss2.art4
|View full text |Cite
|
Sign up to set email alerts
|

Government expenditure and standard of living in an emerging market in Africa–Nigeria

Abstract: The effect of government expenditure on the standard of living has different impact for various level of economies. In this study, we determined the effect of government recurrent and capital expenditure on the standard of living in Nigeria using a test of causation. The long and short run estimates were done by utilizing an Autoregressive Distributive Lag (ARDL) model using data that spanned from 1981 to 2018. Findings/Originality: Precipitously, we asserted that government recurrent and capital expenditure h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…But for the overall level of significance, Prob. (F-Statistic) 0.000000 is less than the 0.05 level of significance; indicating that all the independent variables can jointly influence the dependent variable for the period under review; hence, our null hypotheses are rejected and alternative accepted.Discussion of FindingsThe results of this study confirmed those of other studies in related fields, such asMurita & Taiwo (2011), who examined government spending and economic development in Nigeria between 1970 and 2008 and found a positive relationship between real GDP and recurrent and capital expenditure;Jeff-Anyeneh et al (2020), who looked at government spending and standard of living in an emerging market in Africa-Nigeria-between 1981 and 2008-and found a positive relationship between real GDP and recurrent and capital expenditure.…”
supporting
confidence: 89%
“…But for the overall level of significance, Prob. (F-Statistic) 0.000000 is less than the 0.05 level of significance; indicating that all the independent variables can jointly influence the dependent variable for the period under review; hence, our null hypotheses are rejected and alternative accepted.Discussion of FindingsThe results of this study confirmed those of other studies in related fields, such asMurita & Taiwo (2011), who examined government spending and economic development in Nigeria between 1970 and 2008 and found a positive relationship between real GDP and recurrent and capital expenditure;Jeff-Anyeneh et al (2020), who looked at government spending and standard of living in an emerging market in Africa-Nigeria-between 1981 and 2008-and found a positive relationship between real GDP and recurrent and capital expenditure.…”
supporting
confidence: 89%
“…Tables 3, 4 and 5 reveal that there is a long-run relationship between government expenditure, real gross domestic product, gross fixed capital formation, and national savings. This assertion is based on the fact that the values of the f-statistic of 4.31 (Table 3), 18.81 (Table 4), and 9.04 (Table 5) are higher than the upper and lower bound test of 3.87 and 3.10 respectively at a 5% significance level. On the other hand, no long-run relationship was found between government expenditure and manufacturing capacity utilization in Nigeria as of 3.11 (Table 6) is less than the upper bound test of 3.87.…”
Section: Stationarity Test For the Study Variablesmentioning
confidence: 99%
“…Government revenue provides the financial underpinning for governments to operate and offer services to their populations. Effective management and utilization of government revenue are critical for establishing economic stability, encouraging equitable development, and meeting a nation's diversified requirements (Jeff-Anyeneh et al, 2020).…”
Section: Government Incomementioning
confidence: 99%